การพัฒนาประสิทธิภาพการสื่อสารในองค์กรของคณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏพระนคร - มณีมัย ศุภโ่ชค (Academic Journal Phranakhon Rajabhat University, 2017)
The purpose of this research were to study 1) Investigate the communication within the Faculty of Humanities and Social Science (HUSO), Phranakorn Rajabhat University and 2) Evaluate the communication efficiency within HUSO. A quantitative approach is employed. 113 participants who participated in this study are HUSO faculty members. They are divided into four groups: the administrative board, the government officers (lecturers), the academic staff (lecturers), and the supporting staff. A questionnaire, verified by means of validity and reliability, is utilized to obtain the data. The statistical analysis programs are namely, percentage, mean, and standard deviation (SD.) The results were as follows: 1) Considering the communication within HUSO, Phranakorn Rajabhat University, it appears that a majority of the faculty members pay much attention to announcements informed by HUSO. Communication enables the faculty members receive the news or announcements revealed by HUSO and understand the faculty vision better. In addition, the communication creates the great and effective cooperation and collaboration among HUSO faculty members. They have their own responsibilities and work together in order to achieve the faculty goal. In accordance with the efficiency of HUSO, it appears that it is excellent, based on the three aspects: cooperation (X = 3.944), motivation (3.904), and the organization bond (3.904). As the overall, it is at 3.931. 2) Regarding the communication efficiency within HUSO, as the overall, all three aspects are at the medium level at 3.213: the faculty communication (X = 3.213), information and communication channels (3.50), and recipients (3.097). This may be due to the news or announcements informed by HUSO are not clear and the time is quite tight. The suggested recommendations from this study are revealed. First, the announcements should be clear and informed in advance with an appropriate duration of announcement. Next, the importance of information should be sequenced. Last, the information of the communication channels should be recommended.